KEPENTINGAN INDONESIA MELARANG EKSPOR BENIH LOBSTER KE VIETNAM TAHUN 2015 - Khairani Hilal; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research will explain why Indonesia banned the export of breeding lobster out of state that described is in the study case of a ban on the export of breeding lobster to Vietnam. The purpose of this research is to find out how the mining lobster in Indonesia, and how the necessity of Vietnam about breeding lobster in Indonesia and to discover why Indonesia banned the export of breeding lobster to Vietnam that is listed in the Number 1/PERMEN-KP/2015.The method that used is library research where the data obtained from sources that are relevant to the research problems are discussed. This research uses the perspective of mercantilism, and theories of foreign policy and theories export as well as the concept of national interest according to Jack. Plano and Roy Olton.The result of this research indicate that the purpose of Indonesia stop the export of breeding lobster to Vietnam is to reduce the export volume of breeding lobster because the population of lobster in the wild has declined.Keyword : Mining, Export, Lobster, Breeding Lobster, Over Fishing, Number 1/PERMEN-KP/2015